If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-9)-18=x+26
We move all terms to the left:
4(x-9)-18-(x+26)=0
We multiply parentheses
4x-(x+26)-36-18=0
We get rid of parentheses
4x-x-26-36-18=0
We add all the numbers together, and all the variables
3x-80=0
We move all terms containing x to the left, all other terms to the right
3x=80
x=80/3
x=26+2/3
| 5n^2+19-68=0 | | -14-11d=20-2-9d | | n1=4(n-8) | | 9+3f=21 | | 4(x-18)-9=4x-81 | | 3.93x+15.72=31.44 | | 5w–12=3 | | -14c-1=16-17-14c | | 8x+24=3x-79 | | 4(x-9)-18=4x+26 | | 21/2×n=33/4 | | 118-p=60 | | -14.3=1.4-3d | | 16s+19=-15-10+20s | | -3x+12=2x-20 | | 4=b/3+2 | | 9-(-4)=w/8 | | 7-7x=10-6(x+2) | | 2(x+2)^2+4=34 | | -18-6t=6(-t-3) | | x÷3-6=18 | | 10b-16=-10b+17+20b | | -4x+11(2x-3)=15x+9-17x-2 | | -18v=2-3(6v-16) | | -4.3x+5.7=-7.2 | | 8x-15x+2=3x | | 72+13n=-23 | | 19f-12=-3(-6f+15)+f | | v-2v=3 | | 11=x+10/6 | | 4x^2=24x+108 | | 11-3q=8 |